Manajemen Pembelajaran Program Paket C di PKBM Generasi Amanah - Susanti, Sani; Rahmadani, Siti; Aprilia, Tamara Adisa; Agnesia, Elena; Fellyesa, Rentaida; Pardamean, Brema (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research examines the learning management of the package C program at PKBM Generasi Amanah Sampali Percut Sei Tuan, Medan Estate, Deli Serdang, Deli Serdang Regency, North Sumatra 20371. The aim of this research is to find out how the package C program learning is managed at PKBM Generasi Amanah Deli Serdang Regency . This research uses a qualitative approach and a case study type of research. The subject of the research is the package C manager. This research data was collected using observation, interview and documentation techniques. Data is processed by data reduction, data presentation, as well as conclusions and verification. The results of the research show that this research examines the learning management of the Package C program at PKBM Generasi Amanah, Deli Serdang Regency through several stages, namely: Planning which includes identifying the needs of learning residents, preparing teaching modules. Implementation which includes activities for determining schedules and dividing classes and implementing learning using variations. methods, approaches, media and learning resources; Supervision which includes monitoring and follow-up carried out by the manager or head of the institution.